Autonomic Cooperative Networking - Wódczak, Michał (SpringerBriefs in Computer Science,, 2012)
Cooperative transmission aims to improve the reliability of wireless mobile communications through the use of diversity provided by additional relays assisting in the transmission between the source and destination nodes. This is possible as the rationale behind spatio-temporal processing can be easily mapped onto networked systems. Autonomic Cooperative Networking studies the further evolution of this phenomenon by first involving the network layer routines and then additionally incorporating the notion of autonomic system design.     .